A multifacetada perspectiva religiosa na literatura de Goethe - Farjalla, Marcos (2021)
Johann Wolfgang von Goethe’s religious perspective is a theme that unfolds and demonstrates the wide potential to express the Sacred within his literary works. This understanding takes us, immediately, to the central core of our work, namely: the relation between Religion and Literature. However, to delve deeper into the specificities of the proposed theme – the link between the literary and religious dimensions in Goethe’s works –, it is important to dwell on the analysis of some aspects of modernity, the historical period in which Goethe lived, to understand how his time has reverberated in his thought and in his works. To this end, we developed this research based on a method combined between elements of Phenomenology of Religion and Social Theory of Modernity. In order to demonstrate the amplitude of Religion in Goethe’s works, we seek, within these perspectives, to analyze the link between Literature and Religion in Goethe’s writings having as object of research the following question: Is it possible to attribute a specific religious vision in the midst of such a diverse context? To answer this question, we analyzed three works that, finally, led us to demonstrate and fulfill the objective of this work: “The sufferings of young Werther” (1774); “Elective affinities” (1809) and “Confessions of a beautiful soul” (1796-1797). Starting from the concept of the phenomenon of interference, formulated by Albrecht Wellmer, Art would be, among the value-spheres that depict modernity (Science, Morality and Art), the only one capable of dialoguing with the others, pointing towards a religious totality. In this perspective, Goethe’s works can be read as a path to reconcile man with the truth; element of profound theological meaning through Art – which is the possible appearance of the Sacred.